From the Genetics of Ankylosing Spondylitis to New Biology and Drug Target Discovery - Nancy, Zaarour; Yan, Li; Hui, Shi; Paul, Bowness; Liye, Chen (Frontiers in Immunology, 2021)
Genome-wide association studies (GWAS) have identified 113 single nucleotide polymorphisms (SNPs) affecting the risk of developing ankylosing spondylitis (AS), and an on-going GWAS study will likely identify 100+ new risk loci. The translation of genetic findings to novel disease biology and treatments has been difficult due to the following challenges: 1) difficulties in determining the causal genes regulated by disease-associated SNPs, 2) difficulties in determining the relevant cell-type(s) that causal genes exhibit their function(s), 3) difficulties in determining appropriate cellular contexts to interrogate the functional role of causal genes in disease biology. This review will discuss recent progress and unanswered questions with a focus on these challenges. Additionally, we will review the investigation of biology and the development of drugs related to the IL-23/IL-17 pathway, which has been partially driven by the AS genetics, and discuss what can be learned from these studies for the future functional and translational study of AS-associated genes.